2021
DOI: 10.3390/vaccines9030271
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Regulation in Natural Immunity to HIV

Abstract: Worldwide, most Human Immunodeficiency Virus (HIV) infections are acquired through heterosexual intercourse, and in sub-Saharan Africa, 59% of new HIV infections affect women. Vaccines and microbicides hold promise for preventing the acquisition of HIV. To this end, the study of HIV highly exposed seronegative (HESN) female commercial sex workers (CSWs), who constitute a model of natural immunity to HIV, provides an exceptional opportunity to determine important clues for the development of preventive strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 194 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, since BAFF promotes NOTCH2 expression [7], this molecule is pivotal for the commitment to the MZ B-cell fate [8]. We have reported similar findings for HIV-1-infected Beninese commercial sex workers (CSWs) [9], and Simian Immunodeficiency Virus (SIV)-infected macaques [9], suggesting that excess BAFF and increased frequencies of MZp are a shared trait of HIV-1 infection, not restored via therapy. Moreover, we have shown that people living with HIV (PLHIV) from the Canadian HIV and Aging Cohort Study (CHACS) possess an excess level of BAFF in their blood and concomitant deregulated MZp even after 15 years of therapy.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, since BAFF promotes NOTCH2 expression [7], this molecule is pivotal for the commitment to the MZ B-cell fate [8]. We have reported similar findings for HIV-1-infected Beninese commercial sex workers (CSWs) [9], and Simian Immunodeficiency Virus (SIV)-infected macaques [9], suggesting that excess BAFF and increased frequencies of MZp are a shared trait of HIV-1 infection, not restored via therapy. Moreover, we have shown that people living with HIV (PLHIV) from the Canadian HIV and Aging Cohort Study (CHACS) possess an excess level of BAFF in their blood and concomitant deregulated MZp even after 15 years of therapy.…”
Section: Introductionmentioning
confidence: 67%
“…The following mouse anti-human conjugated mAbs were used to detect extracellular markers on B-cells: APC Anti-CD19, BB515 Anti-IgM, AlexaFluor700anti-CD27, BV421 Anti-CD10 (BD Biosciences), PerCP-eFluor 710 Anti-CD1c (eBioscience, San Diego, CA, USA). We had two different staining cocktails, each identical except for a variation for the PE slot, i.e., (1) PE-anti-CD21 (BD Bioscience) to verify that the MZp were indeed CD21lo when compared to CD21hi MZ, and (2) to verify gp120 binding by using biotinylated fully glycosylated or mutated gp120 (Biotin rgp120 HIV-1 IIIB, ImmunoDx, Woburn, MA, USA) and subsequent PE-conjugated streptavidin (Streptavidin-PE, BD-Biosciences), in presence or absence of a pre-incubation with mannose (5 µg/mL for 40 min on ice), as previously described [9]. Data acquisition was performed with FACSFortessa (BD-Biosciences) for blood PBMC samples, and LSRIIB (BD-Biosciences) for tonsillar samples.…”
Section: Multicolor Flow-cytometry and Gp120 Bindingmentioning
confidence: 99%
“…The role of polymeric nanoparticles in immune-related events has been investigated to regulate several immunogenic signals via immune checkpoint therapies for balancing the immune system and cellular homeostasis. The commonly used immune checkpoint inhibitors in cancer therapies are designed for inhibiting receptors (e.g., programmed cell death-1 (PD-1) receptor) typically expressed in T-cells and the ligand (e.g., PD-L1) expressed by cancer cells [ 105 , 106 , 107 ]. During immune signaling, the PD-1 of the T-cell would be attracted by the cancer cells, which results in the inactivation of T-cells while promoting the tumor-associated cytokine secretion to down-regulate cancer-relevant immune responses and tumor growth [ 108 ].…”
Section: Multifunctional Nanoparticulate Systems For Cancer Immunotherapiesmentioning
confidence: 99%